2011
DOI: 10.1128/jvi.00231-11
|View full text |Cite
|
Sign up to set email alerts
|

Multiploid Inheritance of HIV-1 during Cell-to-Cell Infection

Abstract: During cell-to-cell transmission of human immunodeficiency virus type 1 (HIV-1), many viral particles can be simultaneously transferred from infected to uninfected CD4 T cells through structures called virological synapses (VS). Here we directly examine how cell-free and cell-to-cell infections differ from infections initiated with cell-free virus in the number of genetic copies that are transmitted from one generation to the next, i.e., the genetic inheritance. Following exposure to HIV-1-expressing cells, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
157
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(175 citation statements)
references
References 29 publications
16
157
1
1
Order By: Relevance
“…Studies of plant RNA viruses generally report small effective population sizes during transmission, whereas studies with one plant DNA virus reported a large population of virions during spread in single plant (21)(22)(23). The transmission of HIV between T cells involves transmission of a large number of virions across a virological synapse (2,24). The same concept has been suggested for HSV-1 transmission in T cells (25).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Studies of plant RNA viruses generally report small effective population sizes during transmission, whereas studies with one plant DNA virus reported a large population of virions during spread in single plant (21)(22)(23). The transmission of HIV between T cells involves transmission of a large number of virions across a virological synapse (2,24). The same concept has been suggested for HSV-1 transmission in T cells (25).…”
Section: Discussionmentioning
confidence: 90%
“…In either case, spread from cell to cell often involves direct transmission of infectious particles with no or limited release of infectious particles into the extracellular milieu (1). Cell-to-cell spread of some infections, such as HIV, involves transfer of many viral particles (2), whereas other infections, such those caused by poliovirus, involve transfer of small numbers of particles (3). Virions of members of the alphaherpesvirinae, including the human pathogens HSV-1 and HSV-2, varicella zoster virus, and the animal pathogen pseudorabies virus (PRV) infect epithelial surfaces and transmit efficiently to innervating axons of the peripheral nervous system (PNS) (4).…”
mentioning
confidence: 99%
“…Several different techniques have been used to distinguish target cells from effector cells, such as labeling of cells with fluorescent dyes (21) or mechanical separation of cells by the use of transwells or by continuous shaking of mixed cells (31). However, each of these approaches has its issues.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the precise mechanism, virus transmission and consequent infection are more efficient when the infected cells are in contact with the target cells than when virus is released into body fluids (9,17,18). Furthermore, cell-to-cell infection also alters certain properties of viral infection; for example, it increases the multiplicity of infection (19)(20)(21), enhances the resistance to some antivirals (22,23), allows the virus to bypass potent neutralizing antibodies (24), and contributes to the genetic diversity of HIV (reviewed in reference 25).…”
Section: Discussionmentioning
confidence: 99%
“…Cell-to-cell HIV transmission has often been associated with a more efficient mechanism of infection (16,17,32,34,37). Infected cells bind and interact with target CD4 ϩ T cells in manners that promote virus transmission through the so-called "virological synapse" in which the interaction between CD4 and the HIV envelope glycoprotein plays a prominent role (22,31,35).…”
Section: Discussionmentioning
confidence: 99%